Nursing staff knowledge of COPAP and its correct application in a neonatal intensive care unit (NICU) of a public hospital in the city of Rosario - González , Laura Marcelina; Miranda , Analía (SCT Proceedings in Interdisciplinary Insights and Innovations, 2025)
Skin-to-skin contact (COPAP) is an innovative approach to the care and treatment of premature and low birth weight infants. Warmth, exclusive breastfeeding and the kangaroo position are the basic principles of this method. But most importantly, it is the love and close relationship that develops between the caregiver and the baby that keeps these little ones alive. Meaningful and specific stimulation, whether emotional or organic, will improve and strengthen breathing and heart rate. Therefore, the objective of the study was to determine if there is a relationship between the knowledge of the COPAP method by the nurses under study and its correct application in a Neonatal Intensive Care Unit of a Public sector, between April 2023 to October 2023, a quantitative study was designed, for that a cross-sectional, descriptive, observational, non-experimental, with an evaluation with 16 simple questions and another to record what was observed in each study unit was used. In the results, the nurses showed an average level of knowledge, as a result of deficits in specific items that counteracted the good performance shown in most of the items observed. In contrast to the activity of each nurse as the level of compliance according to the observation of the application of the method was higher